The Chorionic Sculpture of the Eggs of Some Xyleninae (Lepidoptera, Noctuidae) - Dolinskaya, I.V. (Вестник зоологии, 2011)
Eggs of sixteen species of fifteen genera of the subfamily Xyleninae occurring in Ukraine are described and illustrated with scanning electron microphotographs. The diagnostic characters of the genera and species are selected.